Animal Models of Ehlers–Danlos Syndromes: Phenotype, Pathogenesis, and Translational Potential - Vroman, Robin; Malfait, Anne-Marie; Miller, Rachel E.; Malfait, Fransiska; Syx, Delfien (Frontiers in Genetics, 2021)
The Ehlers-Danlos syndromes (EDS) are a group of heritable connective tissues disorders mainly characterized by skin hyperextensibility, joint hypermobility and generalized tissue fragility. Currently, 14 EDS subtypes each with particular phenotypic features are recognized and are caused by genetic defects in 20 different genes. All of these genes are involved in the biosynthesis and/or fibrillogenesis of collagens at some level. Although great progress has been made in elucidating the molecular basis of different EDS subtypes, the pathogenic mechanisms underlying the observed phenotypes remain poorly understood, and consequentially, adequate treatment and management options for these conditions remain scarce. To date, several animal models, mainly mice and zebrafish, have been described with defects in 14 of the 20 hitherto known EDS-associated genes. These models have been instrumental in discerning the functions and roles of the corresponding proteins during development, maturation and repair and in portraying their roles during collagen biosynthesis and/or fibrillogenesis, for some even before their contribution to an EDS phenotype was elucidated. Additionally, extensive phenotypical characterization of these models has shown that they largely phenocopy their human counterparts, with recapitulation of several clinical hallmarks of the corresponding EDS subtype, including dermatological, cardiovascular, musculoskeletal and ocular features, as well as biomechanical and ultrastructural similarities in tissues. In this narrative review, we provide a comprehensive overview of animal models manifesting phenotypes that mimic EDS with a focus on engineered mouse and zebrafish models, and their relevance in past and future EDS research. Additionally, we briefly discuss domestic animals with naturally occurring EDS phenotypes. Collectively, these animal models have only started to reveal glimpses into the pathophysiological aspects associated with EDS and will undoubtably continue to play critical roles in EDS research due to their tremendous potential for pinpointing (common) signaling pathways, unveiling possible therapeutic targets and providing opportunities for preclinical therapeutic interventions.